The Rhythmic Structure of the Poem “Al-Tashira” by Hisham Al-Gakh – A Study of Its Semantic and Aesthetic Dimensions - Rahmani, Zahr Eddine; Belil, Huda (El Omda in Linguistics and Discourse Analysis, 2022)
The poem “Al-Tashira” by the Egyptian poet Hisham Al-Gakh is considered one of the most prominent contemporary poems in both form and content. This is due, on the one hand, to its belonging to free verse poetry, and on the other hand, to its engagement with one of the most important contemporary Arab issues: the fragmentation and dispersion of Arabs, along with its causes, implications, and consequences. This research paper examines and analyzes the poem “Al-Tashira” from a rhythmic perspective, attempting to understand how both its internal and external rhythm contribute to constructing its textual structure and to absorbing its poetic content. This is done in order to convey the intended meaning and achieve the desired emotional and aesthetic impact.